Membangun Dengan Titik Berat Pembangunan Ekonomi Daerah - Sukarno, Bedjo - (Joglo, 2009)
ABSTRACT In district there are various problem about public service like healt, and envorenment prosperity of society. All that determinaned by ability of area to defray most its expenditure. Absolute this time needed a economic democracy climate of can give the contribution to economic development of each, every society segmen. Economic democracy have to be sustained by political structure. Governmental role can do/conduct various area as bussnes, coordinator, stimulator and and fasilitator. Key Word :Â Focus development economic in perspective autonomy. Government clown in regional.